Foot orthoses and physiotherapy in the treatment of patellofemoral pain syndrome: A randomised clinical trial - Vicenzino, Bill (BioMed Central, 2008)
BACKGROUND: Patellofemoral pain syndrome is a highly prevalent musculoskeletal overuse condition that has a significant impact on participation in daily and physical activities. A recent systematic review highlighted the lack of high quality evidence from randomised controlled trials for the conservative management of patellofemoral pain syndrome. Although foot orthoses are a commonly used intervention for patellofemoral pain syndrome, only two pilot studies with short term follow up have been conducted into their clinical efficacy. METHODS/DESIGN: A randomised single-blinded clinical trial will be conducted to investigate the clinical efficacy and cost effectiveness of foot orthoses in the management of patellofemoral pain syndrome. One hundred and seventy-six participants aged 18–40 with anterior or retropatellar knee pain of non-traumatic origin and at least six weeks duration will be recruited from the greater Brisbane area in Queensland, Australia through print, radio and television advertising. Suitable participants will be randomly allocated to receive either foot orthoses, flat insoles, physiotherapy or a combined intervention of foot orthoses and physiotherapy, and will attend six visits with a physiotherapist over a 6 week period. Outcome will be measured at 6, 12 and 52 weeks using primary outcome measures of usual and worst pain visual analogue scale, patient perceived treatment effect, perceived global effect, the Functional Index Questionnaire, and the Anterior Knee Pain Scale. Secondary outcome measures will include the Lower Extremity Functional Scale, McGill Pain Questionnaire, 36-Item Short-Form Health Survey, Hospital Anxiety and Depression Scale, Patient-Specific Functional Scale, Physical Activity Level in the Previous Week, pressure pain threshold and physical measures of step and squat tests. Cost-effectiveness analysis will be based on treatment effectiveness against resource usage recorded in treatment logs and self-reported diaries. DISCUSSION: The randomised clinical trial will utilise high-quality methodologies in accordance with CONSORT guidelines, in order to contribute to the limited knowledge base regarding the clinical efficacy of foot orthoses in the management of patellofemoral pain syndrome, and provide practitioners with high-quality evidence upon which to base clinical decisions. TRIAL REGISTRATION: Australian Clinical Trials Registry ACTRN012605000463673 ClinicalTrials.gov NCT00118521